The Existence of Traditional Games in Early Childhood Learning in the Digital Age - Sulestyaningrum, Dian Rizky; Yuli Kurniawati Sugiyo Pranoto (Universitas Negeri Semarang, 2025)
The existence of traditional games began to erode its existence due to technological developments. This study aims to determine the existence of traditional games in PAUD learning in the current era of digital technology. This research uses qualitative research, with a case study research design. Data collection was done by interview, observation, and documentation. Primary data sources were collected by observation and interview, with three principals, six classroom teachers, and also six parents as informants. Documentation as a secondary data source in the form of photos of traditional game learning implementation, lesson plans, facilities and infrastructure. The research was conducted in three kindergartens in Kendal City, namely Aisyiyah 02 Kindergarten, State Pembina Kindergarten, and Pertiwi Kindergarten. Data analysis used inductive and deductive methods. The results showed that the existence of traditional games in Kendal State Pembina Kindergarten, Pertiwi Kendal Kindergarten, Aisyiyah 02 Kendal Kindergarten still exists and is still introduced to children. However, in learning traditional games there are challenges, the main factor is that many children do not know about traditional games. Because many children today prefer to play gadgets. At home, children are not introduced to traditional games, because parents are busy working. Therefore, the school provides support for the implementation of traditional game learning so that children recognize traditional games